Avaliação agronômica e nutricional do híbrido de sorgo 2011 37 062 em cinco idades - Gabriela Maldini Penna de Mascarenhas Amaral (2014)
Abstract: The objective of this study was to evaluate the agronomic characteristics of sorghum hybrid 2011 37 062, harvested in five ages (87, 91, 95, 98 and 101 days after sowing) as well as the chemical composition, nutritional value, in vitro digestibility (DIVMS), functional groups of lignin characterization in order to establish the best time to harvest this forage. The plants stand did not vary statistically as a function of the plants age, showing an average of 119.990 plants per hectare. Regarding production, in this experiment yields ranging from 34.7 to 18.7 tons per hectare of green matter (PMV) and from 8.18 to 5.38 tons of dry matter (PMS) were found. Also, the digestible matter production (PMSD) ranged from 4.85 to 2.75 ton.MSD / ha. Regarding nutritional value, successive increases were observed in the whole plant dry matter (MS%) (P <0.05) according to the age of the hybrid. The %MS in the culm was constant along the ages of the plant, with an average of 18.24%. The %MS in the leaves ranged between 34 and 59% between the first and the last cut of the plant, showing a significant quadratic relationship, while the variation in %MS in panicle was linear, ranging from 38 to 55%. The percentage of crude protein (%PB) in the whole plant showed a linear decline with advancing age of the plant. The leaf fraction and stem fraction also showed a linear decline with advancing age of harvest. The panicle fraction, on the other hand, presented %CP ranging from 9.24 to 8.63 from the first cut to the fifth one, with a quadratic relationship between CP and plant age. The fiber in neutral detergent (FDN) content of the whole plant increased with advancing plant maturity, ranging from 59.9% in the first cut to 64.5% in the fifth. In the leaves and stem a linear increase of NDF was observed, for panicles, on the other hand, no change was found in NDF content between cuts (average 37.8%). The contents of the fiber in acid detergent (FDA) in the sorghum hybrid 2011 37 062 varied linearly, for the whole plant (PI) and for the leaf and stem fractions. In panicles, the FDA content varied quadractricaly according to the age of harvest. The hemicelluloses contents obtained for the whole plant did not differ significantly according to age of harvest, showing an average of 26.3% of hemicelluloses in the whole plant. The same behavior was observed for the stem, leaves and panicles fractions, with averages of 32.8, 19.2 and 30.5% respectively. The contents of cellulose of sorghum hybrid 2011 37 062 whole plants and fractions showed significant difference between the ages of harvest. The whole plant values ranged from 27 to 30% between the first and last cut showing a linear decrease (P <0.05) according to the stage of plant maturity. For the cellulose content in the panicle, a quadratic relationship between this variable and the cutting age of the plant was observed, while on the leaves and stems a linear increase of cellulose content was observed. The content of cellulose varied from 40 to 45% in stems and 27 to 30% the leaves. Regarding the lignin behavior, no significant differences in the lignin content of whole plant, leaves and panicles were found on the different harvest ages (averages of 7.3, 4.7, and 5.1% respectively). Only the stem fraction increased linearly with percentages ranging 6-8% from the first to fifth cut. The sorghum hybrid 2011 37 062 whole plant showed a DIVMS of 54.2, 49.7, 49.8, 47.4 and 46.3% at the plants harvested 87, 91, 95, 98 and 101 days after sowing, respectively. The stem fraction had DIVMS of 51.4, 43.3, 36.6, 42.2 and 32.2% from the first to the last cut. The panicle and leaf fractions, however, showed a quadratic response (P <0.05) to the increase of plants age of harvest. Regarding the lignin functional groups, in the whole plant, no variation was observed in the monomers composition and the average found was 0.03, 0.04 and 0.04 g per 100 g dry sample of the entire plant for the monomers p-hydroxyphenyl (H), guaiacyl (G) and syringyl (S) respectively. The levels of p-hydroxyphenyl, guaiacyl and syringyl in stems showed a linear increase as a function of age, ranging from 0.03 to 0.04, 0.04 to 0.05 and from 0.04 to 0.06 g per 100 g of dry sample, respectively. The relations syringyl: guaiacyl were 1.0, 1.25, 1.25, 1.20 and 1.25 for the plant harvested 87, 91, 95, 98 and 101 days after sowing. No statistical differences were found for the syringyl content along the hybrid cutting ages, with an average 0.05 g per 100 g dry sample in the panicle. The contents of guaiacyl and p-hydroxyphenyl, however, showed a quadratic relationship with the increasing age of the plant. Observing the values obtained it is possible to conclude that the best time to cut the sorghum hybrid 2011 37 062 is at 87 days after planting, when it is sown in the off-season (February), because at this age the plant showed higher %PB, higher PMS and PMSD without demonstrating increased levels of lignin that can be directly related to the low digestibility.